N‐Spirofused Bicyclic Derivatives of 1‐Deoxynojirimycin: Synthesis and Preliminary Biological Evaluation. Issue 10 (12th July 2016) - D'Orazio, Giuseppe; Martorana, Alessandra M.; Filippi, Giulia; Polissi, Alessandra; Gioia, Luca De; Ferla, Barbara La
Abstract: We synthesized a small library of N‐ spirofused bicyclic derivatives of 1‐deoxynojirimycin (DNJ), as quaternary ammonium salts, through a double SN 2 annulation process. The spirofused rings are of different size and structural characteristics. Preliminary biological evaluation showed no antibacterial activity towards both Gram+ and Gram‐ bacteria. The DNJ derivative bearing a 6 member spirofused cycle revealed a promising inhibitor activity towards amyloglucosidase. Binding energies calculated through docking studies resembled the in vitro capability of such compound and of DNJ to inhibit amyloglucosidase activity, while showing significant difference in the binding poses. Abstract : We synthesised a small library of spirofused iminosugar derivatives of deoxynojyrimycin, and found a promising lead devoid of antibacterial activity while being able to inhibit amyloglucosidase